An Insight into Fatty Acid Composition of Calliergonella cuspidata - Pejin, Boris; Vujisic, Ljubodrag; Sabovljevic, Marko; Tesevic, Vele; Vajs, Vlatka (Asian Journal of Chemistry, 2011)
The fatty acid composition of the moss Calliergonella cuspidata (Hedw.) Loeske (Amblystegiaceae) was preliminary analyzed by gas chromatography (GC FID) and gas chromatography-mass spectrometry (GC-MS). Six fatty acids were identified in its chloroformmethanol extract 1/1: palmitic acid (66.83 %), stearic acid (11.73 %), oleic acid (8.21 %), linolenic acid (6.01 %), α-linolenic acid (3.95 %) and arachidic acid (3.26 %). Arachidonic acid and cis-5,8,11,14,17-eicosapentaenoic acid, typical long-chain polyunsaturated fatty acids for many mosses, were not detected in Calliergonella cuspidata.